Landslide hazards, risks, and disasters - Davies, Timothy R. H. (Hazards and disasters series., 2014)
"Landslides are the most costly geo-hazard in the world, and they're often the cause or the result of other hazards and disasters such as tsunamis, earthquakes, wildfires, and volcanic eruptions. Landslide Hazards, Risks, and Disasters makes a close and detailed examination of major mass movements and provides measures for more thorough and accurate monitoring, prediction, preparedness, and prevention. It takes a geoscientific approach to the topic while also discussing the impacts human-induced causes such as deforestation, blasting, and building construction--underscoring the multi-disciplinary nature of the topic"--Provided by publisher